Diagnostic methods for detection of bone metastases - Łukaszewski, Bartosz; Nazar, Jerzy; Goch, Maciej; Łukaszewska, Marta; Stępiński, Adrian; Jurczyk, Mieczysława U. (Contemporary Oncology/Współczesna Onkologia, 2017)
Skeletal metastases are severe complications in the course of cancer, and they indicate a worse prognosis. The use of modern imaging techniques allows rapid diagnosis of bone metastases. Properly selected diagnostic imaging (scintigraphy, positron emission tomography, whole body MRI) allows us to evaluate the number of metastatic foci in the skeletal system. Complementary imaging examinations (X-ray, computed tomography, magnetic resonance imaging) determine the extent of metastasis and its character: osteolytic, osteoblast, mixed). Hypercalcaemia is a symptom of low specificity for metastatic bone disease (a result of osteolysis); nevertheless, it is a significant complication in oncological treatment and worsens the prognosis of the patient. A biopsy is the final stage of the diagnostic process, which allows us to assess cell and tissue changes. Guided biopsies are performed under the control of musculoskeletal imaging methods (CT, MRI) and they are the most promising tools in bone metastases diagnosis. The development of guided biopsy techniques has led to the conclusion that they should be standard in diagnosing bone metastases. Liquid biopsy (LB) seems to be the most promising diagnostic method for detection of bone metastases. LB based on tumour-specific DNA mutation gives an opportunity for early detection and assessment of the molecular heterogeneity of the overall disease.